Medieval Women, Material Culture, and Power Matilda Plantagenet and her Sisters - Jasperse, Jitske (Gender and Power in the Premodern World, 2020)
This book argues that the impressive range of belongings that can be connected to Duchess Matilda Plantagenet allows us to perceive elite women's performance of power, even when they are largely absent from the official documentary record.